Beginning iPhone Development Exploring the iOS SDK - Nutting, Jack; Olsson, Fredrik; Mark, David; LaMarche, Jeff; Topley, Kim (Apress : Imprint: Apress, 2014)
The team that brought you the bestselling Beginning iPhone Development, the book that taught the world to program on the iPhone, is back again, bringing this definitive guide up-to-date with Apple's latest and greatest new iOS 8 and its SDK, as well as with the latest version of Xcode (6.1). You'll have everything you need to create your very own apps for the latest iOS devices. Every single sample app in the book has been rebuilt from scratch using Xcode 6.1 and the latest 64-bit iOS 8-specific project templates, and designed to take advantage of the latest Xcode features. Assuming only a minimal working knowledge of Objective-C, and written in a friendly, easy-to-follow style, Beginning iPhone Development offers a complete soup-to-nuts course in iPhone, iPad, and iPod touch programming. The book starts with the basics, walking through the process of downloading and installing Xcode 6.1 and the iOS 8 SDK, and then guides you though the creation of your first simple application. From there, you'll learn how to integrate all the interface elements iOS users have come to know and love, such as buttons, switches, pickers, toolbars, and sliders. You'll master a variety of design patterns, from the simplest single view to complex hierarchical drill-downs. The confusing art of table building will be demystified, and you'll learn how to save your data using the iPhone file system. You'll also learn how to save and retrieve your data using a variety of persistence techniques, including Core Data and SQLite. And there's much more!